PENGARUH KUALITAS PRODUK DAN CELEBRITY ENDORSER DI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING PADA APLIKASI SHOPEE - Robby Irvawan; Dini Candani Amelia (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Currently, the cosmetic industry is growing, especially skincare products, be it hair care, body care, and face care products. This study aims to determine how much influence product quality and celebrity endorsers on Instagram social media have on purchasing decisions for Scarlett Whitening products on the Shopee application. This study uses a quantitative method with the population in this study being consumers who have purchased Scarlett Whitening products on the Shopee application, sampling using a non-probability sampling technique with a purposive sampling approach. Tests were carried out using SPSS version 27 including instrument tests, descriptive analysis, classical assumption tests, and hypothesis testing. The results showed that (1) product quality has a significant effect with an R square value of 42.3% on purchasing decisions. (2) celebrity endorser has a significant effect with an R square value of 40.9% on purchasing decisions. (3) product quality and celebrity endorser together have a significant effect on purchasing decisions. This is evidenced by the R square value of 0.501 which indicates that purchasing decisions are influenced by product quality and celebrity endorsers by 50.1% and the remaining 49.9% are influenced by other factors.